Physicochemical Properties And Antimicrobial Activity Of Honey From The Malaysian Stingless Bee Against Selected Pathogenic Bacteria - Salmin Al Mabrouk Ali Al Maghribi (Universiti Sains Islam Malaysia, 2024)
3130041 - FST